Congenital Tuberculosis Due to Confirmed Mycobacterium caprae. Issue 11 (November 2016) - Benavides-Nieto, Marta; Olbrich, Peter; Obando-Santaella, Ignacio; Falcon-Neyra, Lola; Neth, Olaf; Gonzalez-Galan, Veronica; Luque, Rafael
Abstract : Supplemental Digital Content is available in the text.